2017
DOI: 10.4103/ijo.ijo_452_16
|View full text |Cite
|
Sign up to set email alerts
|

The Melaka Hospital cataract complications study analysis of 12,992 eyes

Abstract: Introduction:As in all surgeries, complications during cataract surgery are unavoidable and cause distress to the surgeon and the patient. This study was conducted to know the factors contributing to complications in our settings, to be able to counsel patients about complications and outcomes and to reduce litigations.Materials and Methods:The secondary data analysis was conducted using the National Eye Database from 2007 to 2014. Demographic features, ocular comorbidities, technique of surgery, grade of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Contemporary phacoemulsification has an extremely high level of safety and success, but as previously noted complications still occur in around 5% of cases in teaching hospital series . Preoperative risk stratification systems are effective in identifying cases at higher risk of such intraoperative complications .…”
Section: Discussionmentioning
confidence: 98%
“…Contemporary phacoemulsification has an extremely high level of safety and success, but as previously noted complications still occur in around 5% of cases in teaching hospital series . Preoperative risk stratification systems are effective in identifying cases at higher risk of such intraoperative complications .…”
Section: Discussionmentioning
confidence: 98%
“…Analysis of the published literature over the last 5 years reveals some trends in the contemporary reporting of adverse outcomes in cataract surgery. In this period, of 69 cataract surgery‐related studies published in English language journals, only 11 large studies (with ≥500 participants) reported comprehensive outcomes in terms of commonly reported intraoperative and/or postoperative complications …”
mentioning
confidence: 99%
“…Intraoperative complications that were commonly described in 10 large studies included: capsular tears, dropped or retained nucleus fragment, choroidal, suprachoroidal or vitreous haemorrhage, zonular dehiscence, IOL issues (including IOL drop and exchange) and vitreous loss . However, only two (20%) of these studies reported all six of the most common intraoperative complications: posterior capsular rupture, dropped or retained nucleus fragment, vitreous loss, zonular dehiscence, IOL issues and haemorrhage.…”
mentioning
confidence: 99%
See 2 more Smart Citations